Historical Paradigm In The Face of Religious Radicalism in The21st Century - Wildan Nanda Rahmatullah; Moses Glorino Rumambo Pandin (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
Writing this article aims to discuss the rise of religious radicalism, especially in the 21st century. Then this article is also intended to address the widespread radicalism, especially in Indonesia, according to the paradigm of history. The research method that the author uses is a qualitative method with content analysis through a literature review. The author takes sources from 2 books, 12 journal articles, and 2 news stories from BBC and CNN. In this article, we will discuss the history of radicalism, what the historical paradigm of religious radicalism, how the radicalism impact of religion on people's lives every day, and how prevention is based on the paradigm of history. In this article, the author uses a qualitative approach in the form of content analysis, literature review of 12 journals, 2 books, and 2 news sources from BBC Indonesia and CNN Indonesia. The results of this study are that the authors find that in the 21st century, society is amid unrest due to radicalism. The action is not only in Indonesia but also in several other countries, which is disturbing the peace between religious communities. From this research, the author recommends that this article can be used as a reference in discussing the handling of religious radicalism in social life. The limitation of this research is the lack of data that the author can get due to technical constraints such as limited internet access and social restrictions due to the COVID-19 pandemic.